Accurate modelling based on a subdomain method for heteropolar radial magnetic bearing with a solid rotor. Issue 9 (15th May 2021) - Yu, Chunmin; Deng, Zhiquan; Mei, Lei; Chen, Shangsi; Peng, Cong; Ding, Qiang
Abstract: In this paper, an analytical model based on the subdomain method is proposed for heteropolar radial magnetic bearings (HRMBs) with a solid rotor. Due to the eddy current effects of the solid rotor in varying magnetic fields, accurate analytical models with no eddy current effects and eddy current effects are established for electromagnetic analysis. First, the HRMB is divided into two regions, including the slot region and air region, and three regions, including the slot region, air region, and rotor region, to determine whether eddy currents are considered. The static analytical model and dynamic analytical model are established separately. Furthermore, the air gap magnetic density is derived utilising vector equations and boundary conditions. The analytical model is verified by finite element analysis. Ultimately, the parameters of the HRMB are optimised, while the analytical results are compared with the prototype's experiment results.